Uniform corrosive test for dental materials - Krejčová, Anna; Vavřičková, Lenka; Pokorná, Michaela; Šrámková, Jitka; Dostálová, Taťjána (University of Pardubice, 2013)
The aim of our study was to unify testing of both ceramic and alloy dental materials to one common extraction procedure based on hydrochloric acid for both material groups and find suitable accompanying analytical method. Dental materials typical for routine praxis (eleven dental ceramics and seven metal alloys) were step-wise leached with 0.1 mol l–1 HCl at 37 °C two times for one week and once for two weeks. After the immersion test, the ions released were analysed using the inductively coupled plasma emission spectrometry (ICP-OES) and inductively coupled plasma mass spectrometry (ICP-MS). Detection limits for the ICP-MS method and the ICP-OES method were hundreds to tenths of ng cm–2 and units to tens μg cm–2, respectively. Recoveries for the spiked sample were 94.8-105 % for ICP-OES method and 94.4-108 % for ICP-MS method. The repeatability of the whole analytical procedure including the leaching step, evaluated on the basis of five repetitive extractions of a randomly selected sample was found up to 15 %. In the case of four dental ceramics, significant visual changes of their surface connected with a loss of mass (about 5 %) were observed. The loss of mass was evaluated and compared to international standards and literary data. Multivariate statistical methods proved similarities and differences between materials relating to chemical composition. A uniform corrosion test for ceramic and alloy dental materials was designed. Extracts (0.1 mol l–1 HCl, 37 °C, 168 hours) of ceramics and metal alloys were analysed (ICP-OES).